2017
DOI: 10.1016/j.jmpt.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Chiropractic Care for Older Adults: A Systematic Review and Consensus Update

Abstract: This document provides a summary of evidence-informed best practices for doctors of chiropractic for the evaluation, management, and manual treatment of older adult patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
(105 reference statements)
0
24
0
Order By: Relevance
“…In contrast to frequent recommendations to patients with VDB, manual therapy revealed not to be effective in our target population [40]. Also, the likelihood of injuries following cervical manipulations is increased with age-related diseases like osteoporosis or long-term use of anticoagulant therapy [61] and specific red flags should be assessed before using manual interventions in elderly [62].…”
Section: Main Findingsmentioning
confidence: 88%
“…In contrast to frequent recommendations to patients with VDB, manual therapy revealed not to be effective in our target population [40]. Also, the likelihood of injuries following cervical manipulations is increased with age-related diseases like osteoporosis or long-term use of anticoagulant therapy [61] and specific red flags should be assessed before using manual interventions in elderly [62].…”
Section: Main Findingsmentioning
confidence: 88%
“…In contrast to frequent recommendations to patients with VDB, manual therapy revealed not to be effective in our target population [40]. Considering other literature and the likelihood of injuries following cervical manipulations is increased with age-related diseases like osteoporosis or long-term use of anticoagulant therapy [61] and speci c red ags should be assessed before using manual interventions in elderly [62]. Considering the debatable entity of cervicogenic dizziness [63], MT cannot be recommended for older adults.…”
Section: Main Ndingsmentioning
confidence: 89%
“…Chiropractors who frequently treat older people are more likely to use soft tissue therapies, including trigger point therapy, massage therapy and muscle stretching. While a recent clinical trial reported no serious adverse events from the use of chiropractic spinal manipulative therapy for those aged over 65 years with low back pain, the higher use of more gentle soft tissue therapies for this patient group may relate to practitioner safety concerns when selecting manual therapy methods . Ageing is associated with multiple comorbidities and musculoskeletal changes including increased loss of hip, spine and ankle joint flexibility and osteoporosis .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there is now a growing body of research that has examined the effects of chiropractic management for older people with musculoskeletal complaints such as neck pain low back pain, with and without spinal stenosis and lower limb conditions . The advancement of this research has also been accompanied by the development of practice guidelines for the chiropractic management of older adults …”
Section: Introductionmentioning
confidence: 99%